DAYA HAMBAT DAUN ASAM JAWA (Tamarindus indica) TERHADAP PERTUMBUHAN Salmonella typhi PENYEBAB DEMAM TIFOID - Dini Puspodewi; Sri Darmawati; Endang Triwahyuni Maharani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Tifoid fever is endemic disease who caused by Salmonella typhi bacteria and still to be seriously health problem in Indonesia. The treatment still use antibiotic who can cause resistant if uncontrol using. Tamarind (Tamarindus indica) is plant who can use as medicine. The leaves contain flavonoid, tannin, and saponin who can function as antibacteria. The purpose of this research to know inhibition of tamarind leaves to Salmonella typhi who caused tifoid fever in 25% consentration. This research using old tamrind leaves from Rembang. The leaves was drying and powdering, then soxhletation with eter, extraction with maceration and infused method using distiled water with 25% concentration, then freeze dying and make 1, 2, 3, 4, and 5 mg/25 μL concentration per disc in a row. antibacteri tested with Kirby bauer method. The result of this experiment showing all of variance concentrations at disc can inhibit Salmonella typhi BA07.4 in maceration method as well as in infused method in 25% concentration of tamarind leaves. 5 mg/25 μL concentration has large antibacterial essence showed with existence large zone of inhibition 11,5 mm in maceration method and 14 mm in infused method. infused method of 25% tamarind leaves is more antibacterial essence than maceration method.Keyword : Tamarind leaves, Salmonella typhi, Tifoid fever